Determining cost-effectiveness of lung cancer screening in urban Chinese populations using a state-transition Markov model. Issue 7 (1st July 2021) - Sun, Chengyao; Zhang, Xin; Guo, Sirou; Liu, Yang; Zhou, Liangru; Shi, Jufang; Wu, Ning; Zhai, Zhao; Liu, Guoxiang
Abstract : Objectives: This study analyses the cost-effectiveness of annual low-dose CT (LDCT) screening of high-risk cancer populations in Chinese urban areas. Design: We used a Markov model to evaluate LDCT screening from a sociological perspective. Setting: The data from two large lung cancer screening programmes in China were used. Participants: The sample consisted of 100 000 smokers who underwent annual LDCT screening until age 76. Intervention: The study comprises five screening strategies, with the initial screening ages in both the screening strategies and their corresponding non-screening strategies being 40, 45, 50, 55 and 60 years, respectively. Primary and secondary outcome measures: The incremental cost-effectiveness ratio (ICER) between screening and non-screening strategies at the same initial age was evaluated. Results: In the baseline scenario, compared with those who were not screened, the specific mortality from lung cancer decreased by 18.52%–23.13% among those who underwent screening. The ICER of LDCT screening ranges from US13 056.82 to US15 736.06 per quality-adjusted life year, which is greater than one but less than three times the gross domestic product per capita in China. An initial screening age of 55 years is the most cost-effective strategy. Conclusions: Baseline analysis shows that annual LDCT screening of heavy smokers in Chinese urban areas is likely to be cost-effective. The sensitivity analysis reveals that sensitivity, specificity and the overdiagnosis rate influence the cost-effectiveness of LDCT screening. All scenarios tested demonstrate cost-effectiveness, except for the combination of worst values of sensitivity, specificity and overdiagnosis. Therefore, the cost-effectiveness of a screening strategy depends on the performance of LDCT screenings.